Development of Therapeutic-Grade Small Interfering RNAs by Chemical Engineering - Bramsen, Jesper B.; Kjems, Jørgen (Frontiers in Genetics, 2012)
Recent successes in clinical trials have provided important proof of concept that small interfering RNAs indeed constitute a new promising class of therapeutics. Although great efforts are still needed to ensure efficient means of delivery in vivo, the siRNA molecule itself has been successfully engineered by chemical modification to meet initial challenges regarding specificity, stability and immunogenicity. To date, a great wealth of siRNA architectures and types of chemical modification are available for promoting safe siRNA mediated gene silencing in vivo and, consequently, the choice of design and modification types can be challenging to individual experimenters. Here we review the literature and devise how to improve siRNA performance by structural design and specific chemical modification to ensure potent and specific gene silencing without unwarranted side effects and hereby complement the ongoing efforts to improve cell targeting and delivery by other carrier molecules.